Minsk Military District at Initial Stage of First World War - I. V. Alferova; V. F. Blokhin (Научный диалог, 2022)
The article deals with the issue of organizing the Minsk Military District during the First World War. Attention is paid to the interpretation of the conditions in which the process of formation of this important structure in wartime conditions took place. The authors dwell on the main functions of this territorial entity related to the need to prepare reserves and supply the army in the field. In the presented study, it is shown that in an emergency, for the implementation of these tasks, it was planned to change the system of civilian administration with its subordination to the military leadership of the district. The novelty of the study is seen in the reflection of the problem of reconfiguring the borders of a part of the border military districts, which affected, among other things, the construction of censorship bodies, their ability in practice to adequately and promptly respond to the demands of difficult wartime. It is proved that the “mobility” of the borders of military censorship regions, caused by changes in the operational situation, was reflected in the creation and functioning of the necessary unified district censorship system, which also explains the violations of the “Provisional Regulations on Military Censorship” that occurred within the borders of the district. The stated problem is investigated by the authors of the article on the basis of materials from periodicals and documents stored in local and central archives.